The Influence of Efficiency on Interest Rate Loan in Indonesia Banking in regards to The Implementation of Expected Credit Losses - Syarief Fauzie; Wahyu Sugeng Imam Soeparno; Wahyu Ario Pratomo (Center for Risk Management & Sustainability and RSF Press, 2022)
The purpose of this study is to determine the effect of efficiency on loan interest rates at banks listed on the Indonesia Stock Exchange and their impact before and after the implementation of Expected Credit Losses in Indonesia. The analysis method of this research uses panel data regression with a random effect model to see the effect of efficiency on loan interest rates. The sample of this study uses 22 banks listed on the Indonesia Stock Exchange where the source of research data is from the Bloomberg Finance Lab, Diponegoro University. Efficiency has more influence on loan interest rates before the implementation of expected credit losses than after the implementation. In determining loan interest rates, banks tend to prefer to use credit risk compared to efficiency by looking at the potential profit obtained from looking at the comparison of interbank loan interest rates. These results show that loan interest rates are not easily lowered as a consequence of monetary policy. The results of this study also show that expected credit loss can reduce loan interest rates so that banks are more likely to increase credit risk by increasing loan supply.